2020
DOI: 10.11591/ijeecs.v18.i3.pp1279-1286
|View full text |Cite
|
Sign up to set email alerts
|

Graphene derivative coated QCM-based gas sensor for volatile organic compound (VOC) detection at room temperature

Abstract: <span>Volatile organic compounds (VOCs) affect our daily life through their emission from very common sources such as plants, building materials, paints, pesticides, and fossil fuel burning. The detection of VOCs at room temperature is a prime requirement. The graphene-based gas sensor has the potential to detect these VOC gases due to its attractive features such as high mobility and large surface area. In this work, a graphene-derivative is prepared as a sensing material in order to detect acetone. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Optimization of defect density is an effective way of balancing the sensitivity and recovery rate of a rGO-based gas senor. Another highly promising way of improving the sensitivity and selectivity of graphene-based chemical sensors is via functionalization and hybridization. ,,, These methods offer enormous numbers of graphene-based sensing material combinations with tuned chemical reactivity, such as graphene containing metal and metal oxide nanoparticles, polymers, and small organic molecules. Besides the straightforward use of graphene in electrical sensors, its properties are useful for other VOC sensing devices including colorimetric, optical fiber, and QCM sensors. , In these examples, graphene (or its derivatives) succeeded because of its high surface area and VOC absorption capabilities, not its electrical conductivity. Notably, Cao et al reported the use of a polydiacetylene (PDA)–graphene hybrid for colorimetric VOC sensing.…”
Section: Voc Sensing Materials and Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization of defect density is an effective way of balancing the sensitivity and recovery rate of a rGO-based gas senor. Another highly promising way of improving the sensitivity and selectivity of graphene-based chemical sensors is via functionalization and hybridization. ,,, These methods offer enormous numbers of graphene-based sensing material combinations with tuned chemical reactivity, such as graphene containing metal and metal oxide nanoparticles, polymers, and small organic molecules. Besides the straightforward use of graphene in electrical sensors, its properties are useful for other VOC sensing devices including colorimetric, optical fiber, and QCM sensors. , In these examples, graphene (or its derivatives) succeeded because of its high surface area and VOC absorption capabilities, not its electrical conductivity. Notably, Cao et al reported the use of a polydiacetylene (PDA)–graphene hybrid for colorimetric VOC sensing.…”
Section: Voc Sensing Materials and Structuresmentioning
confidence: 99%
“…265−268 Besides the straightforward use of graphene in electrical sensors, its properties are useful for other VOC sensing devices including colorimetric, 269 optical fiber, 141 and QCM sensors. 270,271 In these examples, graphene (or its derivatives) succeeded because of its high surface area and VOC absorption capabilities, not its electrical conductivity. Notably, Cao et al 269 reported the use of a polydiacetylene (PDA)−graphene hybrid for colorimetric VOC sensing.…”
Section: Voc Sensing Materials and Structuresmentioning
confidence: 99%
“…The QCM gas sensors' quick reaction and recovery periods of 20−30 s have been proven using commercially available rGO thin sensing films. 148 It is claimed that to produce nanostructured detectors GO nanodomains of p-type were carefully inserted into an n-type 3D ZnO nanoarchitecture. These ultraporous nanoheterojunction networks' features were investigated using physical and chemical approaches, demonstrating how GO affects the networks' ability to sense chemicals and light.…”
Section: Graphene-embedded Sensor For Voc Detectionmentioning
confidence: 99%
“…Among them, the QCM-based gas sensor is very effective owing to its beneficial features including accuracy, high sensitivity, and fast response. Also, QCM can be easily integrated with other electronic components [15,16].…”
Section: Introductionmentioning
confidence: 99%